India and Shanghai Cooperation Organization - N. Joshi (Международная аналитика, 2015)
The problem discusses the approaches to security in Central Asian region, especially the threats of instability and Taliban activities in Afghanistan methods of joint resistance to terrorism and other evils. The differences in SCO members’ attitude towards India’s future participation in SCO agenda is being considered. The author doubts that SCO can be regarded as a security provider for the region, it is just an instrument of enhancing regional co-operation in various fields.